Exploring the Influence of Peer Group Interaction on Learning Motivation in Islamic Religious Education - Munjiat, Siti Maryam; Rifa’i, Abdul; Saidah, Zahrotus (Pascasarjana Universitas KH. Abdul Chalim, 2025)
Students' low motivation to learn Islamic Religious Education subjects and the lack of research on the social factors that influence it are crucial gaps in efforts to develop faith-based character education in Indonesia. This study tested the hypothesis that quality peer interaction significantly increases students' intrinsic and extrinsic motivation in Islamic Education learning through social support, collaborative learning, and strengthening religious identity. This study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to 200 students in various junior high schools in Indramayu Regency, and analyzed using linear regression to see the relationship between the independent and dependent variables. The results showed that there is a significant relationship between peer interaction and students' learning motivation level in PAI subjects. The findings make a theoretical contribution to the understanding of the role of peer communities in religious education and offer practical implications for educators to optimize social dynamics in PAI learning, including the implementation of peer-assisted learning strategies, the formation of religious value-based learning communities, and the integration of collaborative activities that support the internalization process of Islamic values.